Genetic trends in seven years of maize breeding at Mozambique's Institute of Agricultural Research - Fato, Pedro; Chauque, Pedro; Senete, Constantino Tomás; Nhamucho, Egas; Sneller, Clay; Mutiga, Samuel Kilonzo; Musundire, Lennin; Gissa, Dagne Wegary; Das, Biswanath; Boddupalli, Prasanna (MDPI, 2025)
Assessing genetic gains from historical data provides insights to improve breeding programs. This study evaluated the Mozambique National Maize Program's (MNMP's) genetic gains using data from advanced germplasm trials conducted at 21 locations between 2014 and 2020. Genetic gains were calculated by regressing the genotypic best linear unbiased estimates of grain yield and complementary agronomic traits against the initial year of genotype evaluation (n = 592). The annual genetic gain was expressed as a percentage of the trait mean. While grain yield, the primary breeding focus, showed no significant improvement, significant gains were observed for the plant height (0.67%), ear height (1.74%), ears per plant (1.31%), ear position coefficient (1.22%), and husk cover (4.7%). Negative genetic gains were detected for the days to anthesis (-0.5%), the anthesis-silking interval or ASI (-9.31%), and stalk lodging (-5.01%). These results indicate that while MNMP did not achieve the desired positive genetic gain for grain yield, progress was made for traits related to plant resilience, particularly the ASI and stalk lodging. MNMP should seek to incorporate new breeding technologies and human resources to enhance genetic gains for grain yield and other key traits in the maize breeding program, while developing and deploying high-yielding, climate-resilient maize varieties to address emerging food security challenges in Mozambique.